Nanomedicine for cancer targeted therapy with autophagy regulation - He, Ketai; Chen, Mingkun; Liu, Jiao; Du, Shufang; Ren, Changyu; Zhang, Jifa (Frontiers in Immunology, 2024)
Nanoparticles have unique physical and chemical properties and are currently widely used in disease diagnosis, drug delivery, and new drug development in biomedicine. In recent years, the role of nanomedical technology in cancer treatment has become increasingly obvious. Autophagy is a multi-step degradation process in cells and an important pathway for material and energy recovery. It is closely related to the occurrence and development of cancer. Because nanomaterials are highly targeted and biosafe, they can be used as carriers to deliver autophagy regulators; in addition to their favorable physicochemical properties, nanomaterials can be employed to carry autophagy inhibitors, reducing the breakdown of chemotherapy drugs by cancer cells and thereby enhancing the drug's efficacy. Furthermore, certain nanomaterials can induce autophagy, triggering oxidative stress-mediated autophagy enhancement and cell apoptosis, thus constraining the progression of cancer cells.There are various types of nanoparticles, including liposomes, micelles, polymers, metal-based materials, and carbon-based materials. The majority of clinically applicable drugs are liposomes, though other materials are currently undergoing continuous optimization.This review begins with the roles of autophagy in tumor treatment, and then focuses on the application of nanomaterials with autophagy-regulating functions in tumor treatment.